Late onset recessive ataxia with Friedreich's disease phenotype. Issue 12 (December 1989) - De Michele, G; Filla, A; Barbieri, F; Perretti, A; Santoro, L; Trombetta, L; Santorelli, F; Campanella, G
Abstract : The Quebec Cooperative Study on Friedreich's ataxia required an onset before age 20 as an obligatory criterion of Friedreich's disease (FD). Harding included patients with onset before 25 years. We studied nine patients with FD phenotype but with onset ranging from 21 to 29 years (mean 24.4). Statistical analysis of the distribution and intrafamilial variation of onset age suggests that late onset Friedreich's disease (LOFD) is a distinct genetic entity or results from modifying genes in some families. Scoliosis was less common in LOFD than FD patients but otherwise the clinical picture was similar.